Efficient modification of peroxydisulfate oxidation reactions of nitrogen-containing heterocycles 6-methyluracil and pyridine - Gimadieva, Alfiya Raisovna; Khazimullina, Yuliya Zulkifovna; Gilimkhanova, Aigiza Aidarovna; Mustafin, Akhat Gaziz:anovich (Beilstein Journal of Organic Chemistry, 2024)
Nitrogen-containing heterocyclic compounds are widely used in pharmacology due to their pronounced biological activities and low toxicities. The introduction of a hydroxy function into uracil and pyridine molecules has led to compounds with antioxidant, anti-inflammatory, and immunomodulatory activity (3-hydroxy-6-methyl-2-ethylpyridine, 5-hydroxy-6-methyluracil, etc.). One of the successful methods for hydroxylation is peroxydisulfate oxidation. By modifying the Elbs reaction through catalysis and the introduction of additional oxidants, we have been able to significantly increase the yields of practically useful compounds.
Keywords: oxidation; 6-methyluracil; peroxydisulfate; phthalocyanine catalysts; pyridine